Coxibs: a significant therapeutic opportunity - Gatti, D.; Adami, S. (Acta Biomedica Atenei Parmensis, 2011)
Pain is the main reason why people decide to see a doctor; hence, the widespread use of anti-inflammatory drugs which were specifically developed to control pain and inflammation. One of the main causes of pain is represented by osteoarticular conditions, the most common one being arthrosis. Paracetamol is universally indicated as the therapy of first choice in degenerative pathologies of the joints, although it is often insufficient to control adequately the clinical picture and less efficacious than anti-inflammatory drugs. These latter, however, especially when taken chronically, exhibit an unfavourable safety profile. The most common side effect of anti-inflammatory drugs is gastric discomfort; coxibs – COX-2 selective inhibitors – were developed to solve this problem. The use of these drugs, relative to conventional NSAIDs, is associated to a significantly lesser gastroduodenal ulcer rate and to fewer clinically relevant complications, as well as to a smaller rate of treatment discontinuation due to gastrointestinal (GI) symptoms. From a clinical and practical standpoint, the use of coxibs is associated to a remarkably reduced risk of gastroduodenal lesions, similar as the one resulting from the combination of a conventional NSAID and a proton-pump inhibitor. By adding a proton-pump inhibitor to a coxib, such risk seems to become virtually non-existent, even in a high risk population and regardless of ASA administration. It is important to stress that the better tolerability of coxibs does not imply an inferior anti-inflammatory and pain-relieving efficacy, especially with regard to etoricoxib, whose efficacy is at least equivalent as other competing NSAIDs, even in quite severe and complex musculoskeletal pain models. This clear-cut advantage of coxibs at gastric level clashed against a documented increased cardiovascular (CV) risk, which led to the much-talked-about withdrawal of rofecoxib from the market. The most credited pathogenetic hypothesis to explain the association between chronic use of coxibs and CV risk seems to be related to a trombophilic effect due to an imbalance of prothrombotic and antithrombotic factors. Several observational and case-control studies, however, led to suspect that conventional NSAIDs share with coxibs an increased cardiovascular risk; such suspicion was experimentally confirmed by the MEDAL trial. In this trial, the cardiovascular risk of thrombosis among patients who were treated on a long-term basis with a coxib (etoricoxib) was shown to be similar as the risk observed in patients receiving a conventional NSAID (diclofenac). In conclusion, coxibs represent a valid therapeutic option in the treatment of patients with osteoarticular conditions. In terms of cardiovascular risk their efficacy is associated to a similar safety profile as conventional NSAIDs, whereas the gastrointestinal risk related to coxibs seems to be significantly lesser.